Trabalho e interação: o problema da emancipação no jovem Habermas - Xavier, Vinicius dos Santos (Universidade Federal de São Carlos, 2014)
The goal of this dissertation is to discuss the two main theoretical sources that Jürgen Habermas uses in his essay "Work and Interaction": the Hegel s philosophy of Spirit of Jena period (1804-1806) and the Marx s theory, especially the labor category. In this sense, beyond criticism resumption of primary sources, the study also presents alternative perspectives to those assumed by Habermas in his youth period, mainly in the 1960s. Therefore, a critique of young Habermas' theory becomes possible, from the central concept of the public sphere to the reasoning of cultural formation in the private sphere, this being the focal point of the essay in question.
Keywords: Habermas, Jürgen, 1929-; Trabalho; Interação; Esfera pública; Esfera privada; Hegel, George Wilhelm Friedrich, 1770-1831; Marx, Karl Heinrich, 1818-1883; Teoria crítica; Jürgen Habermas; Work; Interaction; Public sphere; Private sphere; Cultural formation; Experience; Critical theory; Hegel; Marx; CIENCIAS HUMANAS::FILOSOFIA